Pengaruh Program Adiwiyata terhadap Karakter Peduli Lingkungan Siswa SMP Pembangunan Laboratorium Universitas Negeri Padang (UNP) - Putri Nst, Shelina Rahma; Nefilinda, Nefilinda; Putri, Rozana Eka (UNIVERSITAS NEGERI MAKASSAR, 2023)
This research is motivated by the low participation of students in mutual cooperation and students' lack of awareness in maintaining plants. This study aims to determine and analyze data about the effect of the Adiwiyata Program on the Environmental Care Character Value of Laboratory Development Junior High School Students (UNP). This type of research uses a quantitative approach with a descriptive correlational method. The population in this study was a total of 8 classes with a total population of 211. The technique used is purposive sampling, samples with a total of 54 samples with data analysis techniques descriptive percentage analysis, and conditional tests. The results showed that the average VIII.A class with a percentage of 95% was in the